Poverty associated with anxiety, personality and depression disorders in adults at the "Sarita Colonia" Community Mental Health Center in Callao 2017–2022 - Pedro Martínez Valera; Ada Lucía Gallegos Ruiz Cornejo; Jackeline Valencia; Mauricio Renato Bouroncle Velásquez; Doris Esenarro Vargas; Luis Vega-Mori; Ana Sánchez Medina (Cogent Social Sciences)
This study examined the relationship between poverty and mental health disorders, specifically anxiety, personality, and depression, in 2,399 adults aged 30–59 treated at the Community Mental Health Center ‘Sarita Colonia’ in Callao between 2017 and 2022. Using a positivist paradigm, the research adopted a non-experimental, correlational, cross-sectional design with a quantitative approach and documentary analysis. Results showed no statistically significant association between poverty and mental health disorders (p = .052; F = 2.640; R² = .054). However, ANOVA indicated that poverty might be predicted by anxiety (p = .020; F = 3.378) and depression (p = .026; F = 3.177), but not personality disorders (p = .399; F = .992). The findings highlight the bidirectional relationship between mental health and poverty while challenging the notion that monetary poverty alone predicts mental disorders. This underscores the limitations of relying solely on economic metrics and advocates for the use of multidimensional poverty indicators. Such approaches could provide deeper insights into the complex interplay between mental health and deprivation. These results inform the development of more targeted mental health interventions and public policies, emphasizing the need for comprehensive poverty measures to enhance the effectiveness of strategies addressing mental health disparities.